Contested monuments in a changing heritage landscape: //hapo museum, Freedom Park, Pretoria. Issue 1 (2nd January 2016) - Jacobs, Michele
ABSTRACT: This article looks critically at the //hapo museum at Freedom Park, Pretoria. Freedom Park was constructed as the flagship heritage site for all South Africans, and the reason for its location on Salvokop and the elements that make up the heritage site are discussed. The //hapo museum conforms to the international trend where museums are constructed to provide the visitor with a complete historical and cultural experience of the heritage site. I question whether the //hapo is not just another architectural clone and a ready-made of similar museums around the world, as Baudrillard states. Foucault's notion of the heterotopia is used as the basis to analyse the interior of the //hapo museum. I debate the difficulty of exhibiting artefacts in an enclosed space, disconnected from the temporal effects of the disordered outside where the visitor's own political, cultural and religious background challenges the museum's authority. Memorialising trauma is discussed in terms of the exhibit for Body #1 and Body #2 where, as Herwitz states, the appropriate form of acknowledgement is to resist monumentalisation. I conclude that the endurance of heritage sites such as Freedom Park and the //hapo museum will be determined by their popularity as tourist and heritage sites, rather than the political or ideological reasons for their construction.